SCIENTIFIC ASSESSMENT OF THE EFFECTS OF HYPOTHYROIDISM IN EXPERIMENTAL STUDIES - Azizova Feruza Khusanovna; Mirzamukhamedov Odiljon Xadjiakbarovich; Choriyev Beruniy; Sobirova Dildora Ravshanovna; Shermuxamedov Temur Tokhirovich; Umarova Zulfiya Khosilovna (Galaxy International Interdisciplinary Research Journal, 2023)
The thyroid gland has a hormonal effect on all types of metabolism, determining the individual level of homeostasis, playing the role of an integrative link in neuro-immune-endocrine regulation in the physiological and pathological processes of the body, among which pregnancy occupies a special position.